PENGARUH PENGETAHUAN PERPAJAKAN, KESADARAN WAJIB PAJAK, KUALITAS PELAYANAN FISKUS DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Dimas Ilham; Rr Tjahjaning Poerwati (Jurnal Ilmiah Akuntansi Peradaban, 2023)
This study aims to examine the effect of tax knowledge, taxpayer awareness, tax authorities' service quality, and tax sanctions on taxpayer compliance. The sample in this study was 100 respondents who were obtained through the incidental sampling method. Data is processed with multiple regression. The findings of this study indicate that the variables of knowledge, awareness, service, and sanctions have an effect on taxpayer compliance. The conclusion of this study is that the variables of knowledge, awareness, service and sanctions have a positive and significant relationship with taxpayer compliance. Keywords: Taxpayer Compliance, Knowledge of Taxation, Taxpayer Awareness, Quality of Fiscal Services, Tax Sanctions